Development of Inventory Model to Reduce Total Inventory Costs at RSUD Mentawai - Inaya Izzati; Dida Diah Damayanti (School of Industrial and System Engineering, Telkom University, 2023)
The inventory policy problem is a problem in the inventory system related to how to ensure that eachusage demand can be met at minimal cost. In the healthcare industry, it is imperative that theprocurement and use of stock is not only cost-effective, but also that the required stock is alwaysavailable. Discrepancies between total inventory and usage can lead to damage to BMHP inventoryas the items have expiry dates, as well as excess total inventory costs. The problem of total inventorycosts exceeding the budget occurs because overstock is 83% of the total need, overstock is caused byan excessive number of drug orders purchased. The purpose of this study is to reduce the total cost ofinventory by considering expiry costs, inspection cost, shortage cost, order cost, holding cost usingthe EOQ method. The first stage in this study is to calculate the optimal order quantity value, thenfind the expected number of drug expirations. These results will be used to calculate the total inventorycost of five types of medical materials. for the inspection cost value, if the number of expired medicalmaterials is above 20, the inspection cost value is not equal to zero. The calculation results found thatthe total inventory cost was Rp. 162,904,965, this cost is less than the actual cost of Rp.185,843,346.00 with a difference of 12%.